Seabed corrugations beneath an Antarctic ice shelf revealed by autonomous underwater vehicle survey: Origin and implications for the history of Pine Island Glacier - Graham, Alastair; Dutrieux, Pierre; Vaughan, David G.; Nitsche, Frank O.; Gyllencreutz, Richard; Greenwood, Sarah L.; Larter, Robert D.; Jenkins, Adrian (Journal of Geophysical Research: Earth Surface, 2013)
Ice shelves are critical features in the debate about West Antarctic ice sheet change and sea level rise, both because they limit ice discharge and because they are sensitive to change in the surrounding ocean. The Pine Island Glacier ice shelf has been thinning rapidly since at least the early 1990s, which has caused its trunk to accelerate and retreat. Although the ice shelf front has remained stable for the past six decades, past periods of ice shelf collapse have been inferred from relict seabed "corrugations" (corrugated ridges), preserved 340 km from the glacier in Pine Island Trough. Here we present high-resolution bathymetry gathered by an autonomous underwater vehicle operating beneath an Antarctic ice shelf, which provides evidence of long-term change in Pine Island Glacier. Corrugations and ploughmarks on a sub-ice shelf ridge that was a former grounding line closely resemble those observed offshore, interpreted previously as the result of iceberg grounding. The same interpretation here would indicate a significantly reduced ice shelf extent within the last 11 kyr, implying Holocene glacier retreat beyond present limits, or a past tidewater glacier regime different from today. The alternative, that corrugations were not formed in open water, would question ice shelf collapse events interpreted from the geological record, revealing detail of another bed-shaping process occurring at glacier margins. We assess hypotheses for corrugation formation and suggest periodic grounding of ice shelf keels during glacier unpinning as a viable origin. This interpretation requires neither loss of the ice shelf nor glacier retreat and is consistent with a "stable" grounding-line configuration throughout the Holocene.